SMAC: A Simplified Model of Attention and Capture in Multi-Device Desk-Centric Environments - Li, Zhen; Annett, Michelle; Hinckley, Ken; Wigdor, Daniel (Proceedings of the ACM on Human-Computer Interaction (EICS), 2019)
Prior research has demonstrated that users are increasingly employing multiple devices during daily work. Currently, devices such as keyboards, cell phones, and tablets remain largely unaware of their role within a user’s workflow. As a result, transitioning between devices is tedious, often to the degree that users are discouraged from taking full advantage of the devices they have within reach. This work explores the device ecologies used in desk-centric environments and complies the insights observed into SMAC, a simplified model of attention and capture that emphasizes the role of user-device proxemics, as mediated by hand placement, gaze, and relative body orientation, as well as inter-device proxemics. SMAC illustrates the potential of harnessing the rich, proxemic diversity that exists between users and their device ecologies, while also helping to organize and synthesize the growing body of literature on distributed user interfaces. An evaluation study using SMAC demonstrated that users could easily understand the tenants of user- and inter-device proxemics and found them to be valuable within their workflows.